The Effect of Human Resource Quality and Budgeting Participation on Organizational Culture and Organizational Performance - Astuti, Ni Putu Widya; Yasa, I Nyoman Mahaendra (Universitas Negeri Malang, 2018)
This research aims at understaning the effect of human resource quality and budgeting participation on organizational culture and organizational performance. The sample of research undergoes 126 respondents from 42 Organization of Regional Devices in Tabanan Regency, Bali, Indonesia. This research used SEM analysis of Partial Least Square (PLS). The result show that (1) the quality of human resources has a significant positive relationship with the performance of the organization of the regional apparatus, (2) the participation of budget compilation has no significant positive effect on the organizational culture, (3) the quality of human resources has a significant positive effect on organizational performance (4) the participation of budget compilation has a significant positive influence on the performance of organization of regional apparatus (5) organizational culture has a significant positive effect on the performance of organization, (6) human Resource quality has a significant relationship with the performance of Regional Device Organization through culture organization, (7) budgetary participation on the performance of Regional Devices Organizations through organizational culture. Keywords: budgetary participation; organizational culture; performance organization JEL Codes: D73, H11, O20